DEVELOPING A NEW BOTANIC GARDEN - Richardson, Mark (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2008)
Building a new botanical garden is a valuable opportunity that should be implemented as well as possible. The new botanical garden should not simply a clone of the botanical gardens botanical gardens already established, but it should have its own uniqueness, for example in terms of collecting local plant species. There are several things to be considered that the development of new botanical gardens can have a clear direction and goals, including the founding mission of botanical gardens, involvement in conservation and interpretation, as well as the continuity of the existence of botanical gardens in the future.